2020
DOI: 10.1371/journal.pone.0237021
|View full text |Cite
|
Sign up to set email alerts
|

Public stigma towards prolonged grief disorder: Does diagnostic labeling matter?

Abstract: The recent introduction of prolonged grief disorder (PGD) as a diagnostic category may cause negative social reactions (i.e. public stigma). Vignette experiments demonstrate that persons with both PGD symptoms and a PGD diagnosis elicit more public stigma than persons who experience integrated grief. However, the strength of the influence of the diagnosis itself remains unclear: We aimed to clarify if the diagnostic label PGD produces additional public stigma beyond PGD symptoms. We further compared whether pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 53 publications
(123 reference statements)
2
21
0
Order By: Relevance
“…For example, we did not find a significant effect of the diagnostic status on the attributions of sensitivity and dependency. This seems partly due to the limited power of the present study, given that the effects on dependency were small to moderate, and past studies that did show these effects had larger samples (Eisma, 2018;Eisma et al, 2019;Gonschor et al, 2020). Therefore, we conclude that the findings were generally consistent with prior experiments in European samples.…”
Section: Discussionsupporting
confidence: 81%
“…For example, we did not find a significant effect of the diagnostic status on the attributions of sensitivity and dependency. This seems partly due to the limited power of the present study, given that the effects on dependency were small to moderate, and past studies that did show these effects had larger samples (Eisma, 2018;Eisma et al, 2019;Gonschor et al, 2020). Therefore, we conclude that the findings were generally consistent with prior experiments in European samples.…”
Section: Discussionsupporting
confidence: 81%
“…A standardized vignette described a person with PGD symptoms according to ICD-11 and was presented at the beginning of the interview and the online survey. The vignette was adapted from a vignette of PGD symptoms presented in a study with a German sample without migration background ( 42 ). Assault was chosen as the cause of death because many refugees have experienced traumatic loss ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Research suggests that the new diagnosis of prolonged grief disorder can lead to greater stigmatization. In one study, participants reported increased anger and anxiety, and desired greater social distance when this diagnosis was mentioned ( 39 ). One thing grieving adolescents do not need at this time is increased social distance.…”
Section: The Context Of Grief Pre-covidmentioning
confidence: 99%